Double ectopic parathyroid hyperplasia, intrathyroidal and intrathoracic - Avello Canisto, Francisco (2013)
The case of a patient who satisfactorily underwent left hemithyroidectomy for nodular goiter is reported. Pathology study of the specimen stated enlarged left thyroid gland lobe due to hyperplasic intrathyroidal parathyroid. With this result parathyroid gammagraphy was obtained and a right thoracic capture area was reported. Final diagnosis was ectopic parathyroid hyperplasia of double localization, intrathoracic and intrathyroidal.